Laser Treatment for Urethral Hemangiomas: Report of Three Cases - Soleimani, Mohammad Javad; Shadpour, Pejman; Mehravaran, Kaveh; Kashi, Amir Hossein (Urology Journal, 2017)
To present our experience with coagulation/laser treatment of urethral hemangiomas. Three cases with small to medium sized urethral hemangiomas in penile and posterior urethra presented with hematuria or urethral bloody discharge. All patients were male. They were treated with thermal or Nd-YAG laser coagulation in the first session. Recurrence of hematuria/bloody discharge happened in two patients within one month from the first treatment that was managed with a second session of laser coagulation. No third session of intervention for hematuria/bloody discharge was required in any patient during 10-39 months of follow up. In cases of relapse after thermal or laser coagulation of small to medium sized urethral hemangiomas, after appropriate consultation with the patient, a second session of laser coagulation can be successful before contemplating more invasive measures like open surgery.